Transferring Social Justice Initiatives into Lasallian Schools - Proehl, Rebecca A.; Suzuki, Sawako (Catholic Education: A Journal of Inquiry and Practice, 2009)
This article describes a research project that examined the impact of a Lasallian mission formation program on program participants and their institutions. The study found that the program had a powerful impact on the participants personally, and seventy-one percent (71%) became newly involved or recommitted to social justice initiatives upon returning from the program. Two factors, however, significantly predicted the participants’ level of transfer of learning into action: the availability of social support at their home institution and the applicability of their learning to their work. The article concludes with recommendations to help institutional leaders even more intentionally support participants to bring the lessons learned from mission-formation programs back to their institutions.